ERADICATION OF SOIL MAFIA IN THE POST-COVID-19 PANDEMIC BASED ON NATIONAL LAW AND ISLAMIC LAW RahmatRamadhani - Rahmat Ramadhani (Proceeding International Seminar of Islamic Studies, 2022)
The land mafia takes advantage of land scarcity with land related parties for various purposes. The Ministry of Agrarian Affairs and Spatial Planning (ATR)/National Land Agency (BPN) as the institution most responsible for land administration is still paying attention to the existence of the land mafia. It is necessary to know about the workings of the land mafia who will always seek information about the development of land prices in certain areas by the Local Government such as the Regional Government. This research uses normative law research methods (Normative Law Research). In accordance with the type and nature of the research, the data sources used are secondary data consisting of primary legal materials and secondary legal materials consisting of books, scientific journals, scientific papers and articles that can provide an explanation of primary legal materials. Various efforts were carried out by the government to achieve the goal of eradicating the land mafia, among others through the implementation of land registration as regulated in PP No. 24 of 1997 concerning Land Registration. Indonesia's national law that discusses the eradication of the land mafia is contained in the Technical Instructions of the Ministry of Agrarian Affairs and Spatial Planning/National Land Agency on Prevention and Eradication of Land Mafia. The land mafia is an act of usurping the rights of others, in Islam it is threatened to be hung around his neck from the seven layers of the earth. Sheikh Abdul Azhim bin Badawi al-Khalafi quoted from the Almanhaj page. said, from Sa'id bin Zaid radhiyallahuanhu, he said,